Detoksifikasi Mikotoksin Melalui Optimalisasi Fungsi Rumen dengan Pemberian Ragi (MYCOTOXIN DETOXIFICATION THROUGH OPTIMIZATION THE RUMEN FUNCTION BY YEAST) - Pantaya, Dadik; Wiryawan, Komang Gede; Amirroenas, Dwierra Evvyernie; ., Suryahadi (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
Mycotoxins are toxic metabolites produced by some fungal species commonly found in food and feed,particularly in cereals. In intensive production systems, dairy cattle are commonly fed with cereal-richdiets and, consequently, are more exposed to micotoxins. Besides, such diet is often associated with ahigher risk of rumen acidosis which can also affect the performance and the helath of animal. In addition,the efficacy of microbial detoxification can be reduced during acidosis. For instance, some authors observeda decrease in the number of protozoa that are responsible for the degradation of some mycotoxins. Anotherconsequence of acidosis is the potential modification of ruminal absorption of mycotoxins, which until nowhas received scarce attention. Yeast Saccharomyces cerevisiae, probiotic additives have been shown toreduce the post-feeding drop in rumen pH and to increase the number of ruminal protozoa. This effect canbe positive in reducing the absorption and toxicity of mycotoxins in ruminantia.
Keywords: mycotoxin detoxification; rumen optimization; yeast